Enhancing Infection Control Practices through the Collaboration of Nursing, Nutrition, Physical Therapy, Laboratory, and Radiology Teams - Mansour Shaker Ali Alshehri; Ali Abdullah Alghothimi; Khalid Abdulkhaliq Abdullah Alghamdi; Aliya Abdullah AlBatyain; Ibrahim Saleh Ibrahim Almutyi; Wafa Abdulkhaliq Alghamdi; Huda Amer Safer Alnadawi; Samia Hadi Alkubidy; Nada Abdullah Alhamami; Rehab Mohamed Aldosari; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Infection control as a critical area of practice and delivery of care is inherent to improving client, staff and overall health system outcomes. Although in recent years there have been innovations in medicine and treatment, healthcare-associated infections (HAIs) are still an issue that complicates hospitalization, augments the length of hospital stay and the costs of treatment, increases morbidity and mortality rates. Therefore, the onset of this problem requires the application of a multiprofessional approach, using the experience of nursing, nutrition, physical therapy, laboratory sciences, and radiology. Interdisciplinary cooperation between such teams can greatly improve communication and effectiveness of all infection prevention and control measures, as well as promote a culture of safety within the healthcare organizations. Aim of work: To explore how the synergy among nursing, nutrition, physical therapy, laboratory, and radiology teams enhances infection control practices, focusing on their roles, challenges, and the benefits of teamwork. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Enhancing, Infection Control, Practices, Collaboration, Nursing, Nutrition, Physical Therapy, Laboratory, and Radiology Teams. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Infection control is a concept can be described as complex process that requires concerted effort. Such a nursing care plan of work with clients, involving integration of nursing, nutrition, physical therapy, laboratory services, and radiology significantly defines the possibility to prevent infection, and improve the patient’s outcome. Every specialization brings its own experience, primary with the patients, improvement of their nourishment, diagnostics, and rehabilitation. Multi-disciplinary approach can therefore be recommended as a way through which various healthcare teams can address these infections due to the fact that they have a huge complexity. These factors include misunderstandings, lack of common purpose, and lack formal learning, are detrimental to the smooth running of groups. Over time perhaps due to the constant changes in the health care delivery system, the interconnection between these disciplines will continue to be the bedrock of quality health care delivery especially with a focus on the patient.